PENGARUH TARIF INA CBG’S TINDAKAN CABG TERHADAP KUNJUNGAN PELAYANAN JANTUNG DAN PENDAPATAN DI SANTOSA HOSPITAL BANDUNG CENTRAL - Carolus Ronald; Agus Hadian Rahim; Yusnan Yusuf (Scientia Regendi, 2022)
This study aims to determine and analyze the effect of CABG rates on cardiac service visits and income. The research method used is descriptive analysis and verification. The data collection used is a questionnaire accompanied by observation techniques and literature, Sampling using saturated sampling. Data collection in the field will be carried out in 2022. The data analysis technique uses path analysis.The results showed that there was an effect of CABG action rates on service visits and hospital income in a positive direction, where the higher cardiac service visits would result in increased income at Class A Hospital Santosa Hospital Bandung Central, so it was necessary to evaluate the method of calculating the INA CBGs rate which based on the case base rate method, in order to use a cost of treatment approach based on clinical pathways.